In-Country Free Trade Zone in Post–Conflict Aceh: Illegal Cigarette Trade in Sabang, Indonesia - Lhena Darwin, Rizkika; Akmal, Saiful; Nur Zalikha, Siti; Ahsan, Abdillah; Thalal, Muhammad (Jurnal Ilmiah Peuradeun, 2025)
The implementation of the Sabang Free-Trade Zone (FTZ) has implications for the increasing distribution of illegal cigarettes in the mainland areas of Aceh. It exacerbates state financial losses, community health problems, and the workload on customs to conduct control and supervision. This qualitative study aims to explore how the Free-Trade Zone in Sabang was managed as an instrument for political concession in the Aceh conflict and its quota decision mechanism on illegal cigarettes. Using a grounded qualitative research design, we conducted 12 in-depth interviews with key stakeholders. Four important findings are reflected in this study. First, the management of the Sabang-Free Trade Zone is highly influenced by political aspects and a lack of managerial competence. Second, there is a dilemmatic perspective of the conflicting parties regarding the Sabang FTZ. Third, the quota mechanism related to the distribution of imported cigarettes is not regulated and merely relies on importers’ requests. Lastly, the control and supervision system at the Sabang FTZ is weak. These findings are expected to serve as the foundation for policy recommendations and lessons on the illegal cigarette trade in Indonesia and other post-conflict countries, as well as free trade zones in neighbouring countries like Malaysia, Thailand, Singapore, and the Philippines.